Pengaruh Pendekatan Contextual Teaching and Learning (CTL) Terhadap Motivasi Belajar Siswa MTs Darul Ulum Muhammadiyah Galur - Hidayati, Ika Septi; Setiyaningsih, Evitri (Innovations in Multidisciplinary Education Journal, 2025)
The study entitled “The Effect of Contextual Teaching and Learning (CTL) Approach on Student Learning Motivation at MTs Darul Ulum Muhammadiyah Galur” was motivated by low student learning motivation during lessons. The purpose of this study was to determine the effect of CTL on the learning motivation of ninth-grade students at MTs Darul Ulum Muhammadiyah Galur. This study used a quantitative approach with a quasi-experimental design. The population of this study was ninth-grade students at MTs Darul Ulum Muhammadiyah Galur, and the sample consisted of two classes selected using purposive sampling. Data collection techniques included documentation and questionnaires. Data analysis used descriptive statistical analysis and inferential statistical analysis. The results of the study indicate that there is a significant effect of the CTL approach on the learning motivation of students at MTs Darul Ulum Muhammadiyah Galur, as evidenced by the Sig. (2-tailed) values achieved by the experimental class and the control class, which were 0.00 < 0.05.